Somalia Economic Update, July 2017 : Mobilizing Domestic Revenue to Rebuild Somalia - World Bank Group (World Bank, Nairobi, 2017)
Somalia currently faces large-scale food insecurity, arising from the drought and poor rainfall conditions prevailing across much of the country. Following four consecutive seasons of poor rainfall and low river water levels in large swaths of the country, a severe food crisis has hit in 2017. The drought has led to near total crop failures and reduced rural employment opportunities, widespread shortage of water and pasture, and consequent increases in livestock deaths, which have in turn stretched the country’s coping mechanisms to the brink. Food access diminished rapidly among poor households as staple food prices rose sharply and livestock prices dropped significantly as people engaged in forced sales to cope with the effects of the drought. According to a preliminary Rapid Drought Needs Assessment (RDNA) by World Bank staff, which is based on a triangulation of secondary data1 through remote-sensing techniques, the drought has led to: livestock-related losses of between US$1.3 billion and US$1.7 billion for the period of the drought; crop production losses of up to US$60 million during the period of the drought; and depletion of nominally functional water resources, over 50 percent of which are located within highly drought stressed areas. The new Somali leadership has highlighted drought relief as a top priority. The peaceful and smooth transfer of power has allowed the government to focus quickly on drought and the difficult fiscal situation, highlighting the combined humanitarian and development challenges facing the country. The Humanitarian Response Plan presented at the London Conference in May 2017 increased the appeal to US$1.5 billion to reach 5.5 million people with urgent lifesaving humanitarian assistance. Still, per the UN (2017), the humanitarian situation remained grim for millions as of mid-2017 with a significant risk of famine in many parts of the country.